Risk Perception and Efficacy Beliefs Regarding COVID-19 among Indonesian Pharmacy Students - Lolita, Lolita; Luthfiah Saraswati, Hasna; Muhlis, Muhammad; Ikhsanudin, Azis; Kurniawati, Lindha; Syarifah, Nur Bidayah; Rungprai, Daraporn (Clinical and Pharmaceutical Sciences Journal, 2025)
The SARS-CoV-2 virus first appeared in Wuhan, China, at the end of December 2019. Preventive behavior is necessary to reduce the transmission of this virus, and low risk perception can reduce the implementation of preventive behavior. This study aimed to determine risk perception and efficacy beliefs regarding COVID-19 of pharmacy students at Ahmad Dahlan University, Yogyakarta. A cross-sectional analytic observational approach was utilized; data were collected by distributing online questionnaires. The respondents comprised 406 undergraduate and pharmacist students. The data were analyzed with SPSS version 25.0 to compare the average scores of each independent variable. The mean scores for perceived vulnerability and perceived threat variables were 3.670 and 3.020, respectively, and the mean score for perceived severity was 2.475. The mean scores of response efficacy and self-efficacy were 4.426 and 4.084, respectively. A history of supplement consumption (p = 0.01), having received the first dose of the COVID-19 vaccine (p = 0.02), and parental income (p = 0.045) affected perceived vulnerability. Perceived severity was influenced by gender (p = 0.001), a history of chronic disease (p = 0.041), having received the first dose of the COVID-19 vaccine (p = 0.005), and area of residence (p = 0.043). Perceived threat was influenced by gender (p = 0.005) and having received the first dose of the COVID-19 vaccine (p = 0.029). Efficacy beliefs were influenced by a history of supplement consumption (p < 0.0001 and p = 0.034), having received the first dose of the COVID-19 vaccine (p = 0.037), and implementation of health protocols (p < 0.0001). In conclusion, the respondents’ risk perception was high, whereas their perceived severity was low. The participants also had high efficacy beliefs. Therefore, it is important to focus on pharmacy students risk perception, since they are the main population for social infectious disease prevention and control.